Study on the behavior law when milling the material of the Nomex honeycomb core. (2021) - Zarrouk, Tarik; Salhi, Jamal-Eddine; Atlati, Samir; Nouari, Mohammed; Salhi, Merzouki; Salhi, Najim
Abstract: The technical constraints of the aeronautical and aerospace industry concerning the choice of materials are oriented, among other things, towards lightening structures and reducing consumption. There are many varieties of Nomex sandwich composites on the industrial market. The use of composite honeycomb core structures Nomex has further advanced these years for new generations of Airbus and Boeing aircraft. This expansion currently raises more and more questions for the shaping by milling of these alveolar structures. Due to its manufacture and the constraints associated with its use, the Nomex honeycomb structure is composed of light and flexible walls, which requires the use of machining tools specific. The main difficulties that accompany their machining are related to the property's structural elements of the alveolar core, particularly the weakness of flexural rigidity local cell walls, the lightness of the material and its low density. The main objective of this article is to present a robust numerical model to predict and analyze the parameters influencing the milling of this type of structure. This work aims to analyze the effect of tool geometry and wall thickness on cutting forces using the isotropic elastoplastic approach.